FRANJO TUĐMAN IN THE SERBIAN PRESS FROM THE FIRST GENERAL HDZ ASSEMBLY TO THE BEGINNING OF THE SERB REBELLION IN CROATIA (Review of Croatian History, 2021)
This work is devoted to analyzing, in the context of political propaganda and by using selected newspaper and magazine articles, the portrayal of Franjo Tuđman in the Serbian press in the period from the First General Assembly of the HDZ to the beginning of the Serb rebellion in Croatia. The role and purpose of the newspaper and magazine articles in creating a negative image of Franjo Tuđman through a process of artificially constructing an illusion of an enemy is shown and explained. The Serbian press, from the beginning, portrayed Franjo Tuđman as a Croatian nationalist and an enemy of the Serbian people. The media campaign against Franjo Tuđman seamlessly blended in with the patterns of the Greater Serbian propaganda campaign against Croatia. That broader campaign began in mid-1989 and steadily gathered pace. It was fuelled, first and foremost, by negative depictions of the Ustasha regime and the Independent State of Croatia (NDH).